The Democracy-Promotion Metanarrative as a Set of Frames: Is There an Indigenous Counter-Narrative? - Hajer Ben Hadj Salem (Religions, 2025)
The Tunisian uprisings projected an elusive surrealistic scene that was an aberration in a part of the world where Islamic ideology had been considered the only rallying force and a midwife for regime change. However, this sense of exceptionalism was short-lived, as the religiously zealous Islamist expats and their militant executive wings infiltrated the power vacuum to resume their suspended Islamization project of the 1980s. Brandishing electoral “legitimacy”, they attempted to reframe the bourgeoning indigenous democratization project, rooted in an evolving Tunisian intellectual and cultural heritage, along the neocolonial ideological underpinnings of the “Arab Spring” metanarrative, which proffers the thesis that democracy can be promoted in the Muslim world through so-called “Moderate Muslims”. This paper challenges this dominant narrative by offering a counter-narrative about the political transition in Tunisia. It takes stock of the multidisciplinary conceptual and analytical frameworks elaborated upon in postcolonial theory, social movement theory, cognitive neuroscience theories, and digital communication theories. It draws heavily on socio-narrative translation theory. The corpus analyzed in this work consists of disparate yet corroborating narratives cutting across modes, genres, and cultural and linguistic boundaries, and is grounded in insider participant observation. This work opens an alternative inquiry into how the processes of cross-cultural knowledge production and the power dynamics they sustain have helped shape the course of the transition since 2011.